ENHANCING THE STUDENTS’ READING COMPREHENSION BY USING CONTEXTUAL TEACHING & LEARNING (CTL) - Refai - Refai (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2013)
The objective of the study was to find out if Contextual Teaching and Learning (CTL) can develop the 12th Grade Students’ reading comprehension. The findings showed that CTL is able to enhance the students’ reading comprehension. Before the teacher applied CTL in the class, he activated the students’ schemata of understanding some of the English texts, then, he addressed the implementated procedure of the strategy, in addition, the students started to read the text and situated the text to the real-life, then they related the content of the text by answering “What, Where, Why” and the important aspects of understanding the text. At last, the students got post-test of reading comprehension, and the teacher determined the students’ scores.